Effects Of Greenhouse Technology on Tomato Growth and Yield (Production) In the Transitional Zone of Ghana (Journal of Science and Technology, 2024)
Greenhouse technology has been recognised for its potential in promoting food security, reducing greenhouse gas emissions, efficient water resources management, and improved environmental sustainability globally. Despite the numerous benefits it offers, farmers have still not fully embraced its usage. Little information also exists regarding how adopting the technology can help promote tomato productivity in the midst of climate change and land scarcity. This has not only resulted in vast land degradation but also a persistent importation of tomatoes at exorbitant cost. This study aims to investigate how greenhouse technology can be utilised to promote tomato productivity and eradicate poverty within limited land resources. The experiment was conducted using a randomised complete block design with 45 tomato seedlings planted in each environment and the parameters measured were tomato growth, yield, and value-cost ratio. The results showed that greenhouse technology significantly increased yield of tomatoes, with higher marginal returns than the open field. This indicates that should GT be adopted, limited amount of land could be needed to produce to keep pace with local demand, halt poverty, hunger, and tomato importations. The study concludes that adopting GT has potentials in increasing tomato productivity with limited land size. The technology is an opportunity to help achieve the overarching goal of ending poverty, hunger, and malnutrition. Future study is needed on farmers’ adoption ability, sustainability and financial viability of the technology by using revenue and cost streams covering the entire economic life of the greenhouse production system in the transitional zone of Ghana.